Mid-Holocene intensification of Southern Hemisphere westerly winds and implications for regional climate dynamics. (1st April 2023) - Tamhane, Jamie; Thomas, Zoë A.; Cadd, Haidee; Harris, Matthew R.P.; Turney, Chris; Marjo, Christopher E.; Wang, Huixin; Akter, Rabeya; Panaretos, Panayiotis; Halim, Amalia; Gadd, Patricia S.; Carter, Stefanie; et al.
Abstract: The Southern Hemisphere westerly winds (SWW), a belt of strong zonal winds in the mid-latitudes, play a key role in Southern Hemisphere climate variability. Recent intensification and southwards migration of the SWW is projected to continue due to anthropogenic climate change and despite a recovering Antarctic ozone hole, impacting regional hydroclimate, ocean circulation and carbon cycling. Despite the importance of the SWW, our understanding of their behaviour on centennial to millennial timescales is limited by the inherently short observational record and limited palaeo-archive agreement on the wind belt's Holocene dynamics. Here we utilise dust flux, Itrax core scanning, rare earth element composition and HYSPLIT particle modelling to present a 8700-year (10, 500–1700 cal yr BP) reconstruction of local SWW intensity from a Falkland Islands (Islas Malvinas) peat sediment core which, along with other reconstructions, we interpret in a regional South Atlantic and hemispheric context. We find increased dust deposition and variability from ca. 5700 cal yr BP, signalling an intensification and possible southwards shift of the SWW, though Patagonia likely remains the primary distal dust source throughout our record. Additionally, we identify asymmetric behaviour in the SWW belt from 3000 to 1700 cal yr BP over southern South America and the southwest Atlantic. In alignment with these findings, we propose a possible eastwards projection of the Amundsen Sea Low (ASL) into the South Atlantic during this period. Two volcanic eruptions, likely from Mt Burney (ca. 9700 cal yr BP) and Mt Hudson (ca. 4100 cal yr BP), are captured as cryptotephra deposits in the record. Our precisely dated, high-resolution multiproxy record of South Atlantic wind-blown transport provides an important new dataset that accurately constrains SWW Holocene variability over the Falkland Islands. Highlights: 8700-year reconstruction of SWW intensity from a Falkland Islands peat sediment core. Utilise dust flux, Itrax core scanning, REE composition and HYSPLIT modelling. We find increased dust deposition and variability from ca. 5700 cal yr BP. We interpret this as an intensification and possible southwards shift of the SWW.